Teaching English Online Through the Use of Instagram in the New Normal Era of Covid-19 - Bestari, Ade Christanty Yudha; Faiza, Dinar; Mayekti, Meilina Haris (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2023)
Everyone has an Instagram account in this digital age. Lecturers use Instagram as a medium for developing English language teaching. The lecturer asked the students to write their ideas in English on Instagram caption. This study presents an analysis of English skills in teaching English online through the use of Instagram in the New Normal era of Covid-19. The data will be analyzed using quantitative and qualitative research standards. The first data of this quantitative study was taken from the Survey through a questionnaire. Survey is a procedure in quantitative research that involves the use of a questionnaire to explore population characteristics, attitudes, behaviors, and opinions. Then, the researcher used qualitative research to serve the results of the interview data. The results of this study are first, that English skills are dominant in teaching English online. Second, students' perceptions of English language skills that are difficult to develop in online teaching through the use of Instagram in the new normal era of covid-19. Third, Instagram is a media solution for teaching English online for students.